P The Effect of Foot Massage Using Olive Oil on Post–Cesarean Section Wound Pain - Maulida, Ayu Ires; Wulandari, Catur Leny; Sutrisminah, Emi (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2026)
Introduction: This study aimed to determine the effect of foot massage with olive oil on post-cesarean section wound pain in the postpartum room of RSI PKU Muhammadiyah Pekajangan, Pekalongan Regency. Method: This study employed a quantitative method using a pre-experimental design with a one-group pretest-posttest approach. The dependent variable (post-cesarean section wound pain) was measured before and after the intervention (foot massage with olive oil) in the same group of participants. This study used a nonprobability sampling method with a purposive sampling technique. The sample in this study was 32 participants. After collecting the data, it was processed and analyzed using SPSS. The non-parametric statistical analysis test, Wilcoxon signed-rank test, was used to test the comparative hypothesis of two paired samples with a significance level of 95% (α = 0.05). The results: showed a statistically significant reduction in pain intensity after the intervention (p = 0.000). Conclusion: foot massage with olive oil has a significant effect on reducing post-cesarean section wound pain in the postpartum ward of RSI PKU Muhammadiyah Pekajangan, Pekalongan Regency, in 2025.